2010
DOI: 10.1074/jbc.m109.067215
|View full text |Cite
|
Sign up to set email alerts
|

Heme-responsive DNA Binding by the Global Iron Regulator Irr from Rhizobium leguminosarum

Abstract: Heme, a physiologically crucial form of iron, is a cofactor for a very wide range of proteins and enzymes. These include DNA regulatory proteins in which heme is a sensor to which an analyte molecule binds, effecting a change in the DNA binding affinity of the regulator. Given that heme, and more generally iron, must be carefully regulated, it is surprising that there are no examples yet in bacteria in which heme itself is sensed directly by a reversibly binding DNA regulatory protein. Here we show that the Rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 54 publications
0
60
0
Order By: Relevance
“…The N-terminal heme regulatory motif of the B. japonicum Irr protein is absent in many irr homologues (61). In addition, it has been shown in R. leguminosarum that while Irr appears to be a heme binding protein, it differs from the B. japonicum homologue in that it is stable in the presence of heme (60). Finally, it has been shown that the HHH motif in the Irr protein from R. leguminosarum is necessary for binding to DNA, while the role of the HHH motif from B. japonicum remains untested (60).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The N-terminal heme regulatory motif of the B. japonicum Irr protein is absent in many irr homologues (61). In addition, it has been shown in R. leguminosarum that while Irr appears to be a heme binding protein, it differs from the B. japonicum homologue in that it is stable in the presence of heme (60). Finally, it has been shown that the HHH motif in the Irr protein from R. leguminosarum is necessary for binding to DNA, while the role of the HHH motif from B. japonicum remains untested (60).…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of the HHH motif results in a stable Irr protein, while mutation of the HRM reduces the rate of degradation (73). The general applicability of this model to other Irr proteins has recently been called into question (60). The N-terminal heme regulatory motif of the B. japonicum Irr protein is absent in many irr homologues (61).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies described by Martínez et al (10) suggest that a similar relationship between cellular iron levels and Irr stability may also exist in B. abortus 2308. However, recent studies with another alphaproteobacterium, Rhizobium leguminosarum, suggest that Irr activity in this bacterium is modulated by heme, and Irr is inactivated, but not degraded, when cellular iron levels increase (26). Instead, heme binding to the R. leguminosarum Irr inhibits its DNA binding capacity.…”
Section: Vol 193 2011mentioning
confidence: 98%
“…Instead, heme binding to the R. leguminosarum Irr inhibits its DNA binding capacity. Distinguishing between these two models for regulating Irr function is important because the Brucella Irr, like the R. leguminsarum Irr, does not possess the heme regulatory element (GCPWAD) in its N terminus that is required for the iron-responsive degradation of Irr in Bradyrhizobium japonicum (19,26). As shown in Fig.…”
Section: Vol 193 2011mentioning
confidence: 99%